Making mobile work - Kasher, Robert (O'Reilly Media, 2008)
"It seems that every week another major announcement is made in the sphere of mobile communications regarding a new product, service or opportunity. How can content providers of all types but particularly those in publishing take advantage of the growing opportunity mobile poses in reaching new markets both domestically and internationally"--Resource description page.